Estudo histopatológico da implantação de nervo periférico no osso - Varanda, Denis [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction - There are several surgical techniques for treatment of painful amputation neuroma. However no consensus has already been reached on the most effective treatment. Burying the neuroma or the nerve in the bone is one of the surgeries which provides good clinical findings. However, there is no deep knowledge of what happens to the nerve or buried neuroma in the bone. Objectives - The objectives of this study were to develop an experimental model of this surgical technique and to morphologically analyze the destiny of the implanted nerve in the bone. Materials and Methods - A total of 24 four rats underwent implantation of the caudal tibial nerve in the distal third of the femur. They were histologically studied in the periods of 1, 3, 6, 13, 24 and 28 weeks by optical microscopy. Conclusion - The analyses of the images showed that implantation of the nerve in the bone triggers an inflammatory response which evolves from the acute phase to the nerve-bone integration with no formation of neuroma

Introdução - Há diversas técnicas cirúrgicas para o tratamento dos neuromas doloridos, porém não há consenso em relação a mais eficaz. A implantação do neuroma ou do nervo dentro do osso é uma das cirurgias que proporciona bons resultados clínicos. Contudo, não há conhecimento detalhado sobre o destino do nervo ou neuroma implantado no osso. Objetivos - Os objetivos do estudo foram desenvolver modelo experimental de implantação de nervo no osso e analisar morfologicamente o destino no nervo implantado no osso. Material e Métodos - 24 ratos foram submetidos à implantação do nervo tibial caudal no terço distal do fêmur e estudados histológicamente nos períodos de 1, 3, 6, 13, 24 e 28 semanas por meio de microscopia ótica. Conclusões - Análise das imagens demonstrou que a implantação do nervo no osso desencadeia processo inflamatório que evolui da fase aguda para integração nervo-osso, sem formação de neuroma
Keywords: Neoplasias; Nervos periféricos; Femur - Cirurgia; Cirurgia - Tecnica; Ossos - Cirurgia; Nerves, Peripheral